Analisis Minimasi Waktu Operasional Bar Restoran Ever Green Melalui Pendekatan Algoritma Metode Hungaria - nabila khairani; Yunita Juniarti Dewi; Sindi Ramadani; Ahmad Albar Tanjung (Jurnal Ekonomi dan Bisnis Digital, 2026)
Competition in the culinary industry requires restaurants not only to excel in product quality but also to manage their resources efficiently. This study aims to optimize employee assignment in the bar section of Ever Green Restaurant to minimize operational time using a scientific approach. The research employs a quantitative approach with a case study design, in which primary data were obtained through direct observation and time measurements of five bar employees performing five different beverage-related tasks. The collected data were then analyzed using the Hungarian Method based on the one man one task principle. The results indicate that the application of the Hungarian Method produces an optimal assignment configuration with a minimum operational time of 17 minutes. This assignment allocates each employee to the task most aligned with their competencies, thereby reducing waiting time and workload imbalance. These findings suggest that the application of optimization methods provides a more objective approach to improving operational efficiency and service quality in restaurants.